What the Framework Convention on Climate Change Teaches Us About Cooperation on Climate Change - Victor, David G. (2016)
Arild Underdal has been at the center of an important community of scholars studying global environmental governance. Since the 1990s that community, along with many other scholars globally, has offered important insights into the design and management of international institutions that can lead to more effective management of environmental problems. At the same time, diplomats have made multiple attempts to create institutions to manage the dangers of climate change. This essay looks at what has been learned by both communities—scholars and practitioners—as their efforts co-evolved. It appears that despite a wealth of possible insights into making cooperation effective very few of the lessons offered by scholars had much impact during the first two decades of climate change diplomacy. Indeed, basic concepts from cooperation theory and evidence from case studies—many developed in Arild’s orbit—can explain why those two decades achieved very little real cooperation. The new Paris agreement may be changing all that and much better reflects insights from scholars about how to build effective international institutions. Success in the Paris process is far from assured and scholars can contribute a lot more with a more strategic view of when and how they have an impact.